Relationship between donor fraction cell‐free DNA and clinical rejection in heart transplantation. (8th March 2022) - Deshpande, Shriprasad R.; Zangwill, Steven D.; Kindel, Steven J.; Schroder, Jacob N.; Bichell, David P.; Wigger, Mark A.; Richmond, Marc E.; Knecht, Kenneth R.; Pahl, Elfriede; Gaglianello, Nunzio A.; Mahle, William T.; Stamm, Karl D.; et al.
Abstract: Background: Clinical rejection (CR) defined as decision to treat clinically suspected rejection with change in immunotherapy based on clinical presentation with or without diagnostic biopsy findings is an important part of care in heart transplantation. We sought to assess the utility of donor fraction cell‐free DNA (DF cfDNA) in CR and the utility of serial DF cfDNA in CR patients in predicting outcomes of clinical interest. Methods: Patients with heart transplantation were enrolled in two sequential, multi‐center, prospective observational studies. Blood samples were collected for surveillance or clinical events. Clinicians were blinded to the results of DF cfDNA. Results: A total of 835 samples from 269 subjects (57% pediatric) were included for this analysis, including 28 samples associated with CR were analyzed. Median DF cfDNA was 0.43 (IQR 0.15, 1.36)% for CR and 0.10 (IQR 0.07, 0.16)% for healthy controls ( p < .0001). At cutoff value of 0.13%, the area under curve (AUC) was 0.82, sensitivity of 0.86, specificity of 0.67, and negative predictive value of 0.99. There was serial decline in DF cfDNA post‐therapy, however, those with cardiovascular events (cardiac arrest, need for mechanical support or death) showed significantly higher levels of DF cfDNA on Day 0 (2.11 vs 0.31%) and Day 14 (0.51 vs 0.22%) compared to those who did not have such an event ( p < .0001). Conclusion: DF cfDNA has excellent agreement with clinical rejection and, importantly, serial measurement of DF cfDNA predict clinically significant outcomes post treatment for rejection in these patients.